2015
DOI: 10.1038/labinvest.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen suppresses hepatocellular carcinoma cells through ERβ-mediated upregulation of the NLRP3 inflammasome

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. The incidence of HCC is strikingly higher in males than in females. The remarkable gender disparity suggests an important role for sex hormones in HCC pathogenesis. Recently, estrogen has emerged as a protective factor in the development and progression of HCC, but whether it prevents and attenuates HCC, and the mechanism of protection, have not been elucidated. The present study shows that expression of estrogen receptor (ER) β w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 32 publications
3
90
1
Order By: Relevance
“…The NALP3 gene has an essential role in endometriosis progression because NALP3 −/− mice have a defect in ectopic lesion growth under endometriosis. ERβ involves in upregulation of NALP3 inflammasome in hepatocellular carcinoma cells upon estrogen stimulation even though the interaction of ERβ to NALP3 is not clearly demonstrated (Wei et al, 2015). Here, we revealed that ERβ interacts with inflammasome components and enhances inflammasome activity through the activation of caspase 1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The NALP3 gene has an essential role in endometriosis progression because NALP3 −/− mice have a defect in ectopic lesion growth under endometriosis. ERβ involves in upregulation of NALP3 inflammasome in hepatocellular carcinoma cells upon estrogen stimulation even though the interaction of ERβ to NALP3 is not clearly demonstrated (Wei et al, 2015). Here, we revealed that ERβ interacts with inflammasome components and enhances inflammasome activity through the activation of caspase 1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that estrogen may inhibit hepatic tumor growth and progression by acting as a suppressor for alternative activation of tumor-associated macrophages and inhibiting the Jak1-Stat6 signaling pathway 31 . A recent report provided new insight into the protection of estrogen in HCC via the regulation of NLRP3 inflammasome by estrogen through the ER β/ MARK pathway 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation status of cells were detected at different time points, including 0, 12 h, 24 h, 36 h, 48 h, and 72 h. Cell invasion and colony formation assay were performed as described before [26, 27]. …”
Section: Methodsmentioning
confidence: 99%